Effects of the Blended Learning Model on Learning Achievement in Chairball Sports Course for Seventh Grade Student - Yodjan, Thawatchai; Chimwong, Luxsamee (Ratchaphruek Journal, 2023)
The purposes of this quasi-experimental research were: 1) To compare the effects of blended learning management in chairball course toward to the students’ learning achievement between the experimental group and the control group and from pre-test to post-test; 2) To compare the effect of blended learning management in chairball course on the students’ learning achievement; 3) To study the students’ satisfaction. The sample consisted of 80 seventh grade students from Triam Udom Suksa Suwinthawong School, divided into two groups: 40 students for the experimental group and 40 students for a control group. Each group was observed eight times for 50 minutes per session. The instruments in this research were a blended and traditional learning model management plan, a general knowledge test, a skills assessment form for passing and receiving the ball, including three skills, and a questionnaire to assess student satisfaction towards blended learning management. Data were analyzed by mean, standard deviation, and a t-test for dependent and independent samples. The results of the research were: 1) the learning achievement of the experimental and control group after the study were higher than before with a statistical significance of .05; 2) post-learning achievement of the experimental group was statistically significantly higher than that of the control group at .05; and 3) overall satisfaction of the students towards the blended learning management of chairball course was at the highest level.